2014
DOI: 10.1016/j.molcel.2014.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous miRNA and Target Concentrations Determine Susceptibility to Potential ceRNA Competition

Abstract: SUMMARY Target competition (ceRNA crosstalk) within miRNA-regulated gene networks has been proposed to influence biological systems. To assess target competition, we characterize and quantitate miRNA networks in two cell types. Argonaute iCLIP reveals that hierarchical binding of high- to low-affinity miRNA targets is a key characteristic of in vivo activity. Quantification of cellular miRNA and mRNA/ncRNA target pool levels indicates that miRNA:target pool ratios and an affinity partitioned target pool accura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
402
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 378 publications
(431 citation statements)
references
References 57 publications
28
402
1
Order By: Relevance
“…Hence, a better understanding of the role of competing endogenous RNAs (ceRNAs) in miRNA mechanisms is urgently needed. We predict such a phenomenon might take place only at high TPM, given the preferential interaction of a miRNA with high-affinity targets and the reduction of the effective target pool, as previously observed (Bosson et al 2014).…”
Section: High Complementary Targets and Enzymatic Activities Are Detesupporting
confidence: 74%
See 1 more Smart Citation
“…Hence, a better understanding of the role of competing endogenous RNAs (ceRNAs) in miRNA mechanisms is urgently needed. We predict such a phenomenon might take place only at high TPM, given the preferential interaction of a miRNA with high-affinity targets and the reduction of the effective target pool, as previously observed (Bosson et al 2014).…”
Section: High Complementary Targets and Enzymatic Activities Are Detesupporting
confidence: 74%
“…Although these correlations are strong, more direct evidence will be required to demonstrate that the behavior of "fast" miRNAs depends on the level of their 3 ′ complementary targets. Of note, several studies pointed out the existence of a threshold in target repression that depends on miRNA expression and target abundance (Mukherji et al 2011;Mullokandov et al 2012;Bosson et al 2014), suggesting that the activity of a miRNA on its target decreases sharply at high TPM ratios. A relevant implication of our study is the theoretical possibility to switch from "high" to "low" TPM and thus modify the activity and the decay of miRNAs.…”
Section: High Complementary Targets and Enzymatic Activities Are Detementioning
confidence: 99%
“…In HCC, HULC functions as an endogenous sponge that suppresses the activity of miR-372 (17). Meanwhile, emerging studies showed that ceRNAs cannot alter miRNA function in vivo (36,37). They demonstrated that it is difficult to achieve sufficiently high expression of a ceRNA to significantly derepress the mRNAs regulated by that miRNA in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, BRLF1/BZLF1, and BAD do not appear to exert a ceRNA effect on each other. ceRNA effects are argued to be induced only in miRNA families with low total miRNA-to-target ratios (43). Furthermore, it was recently suggested that modulation of miRNA target abundance is unlikely to cause significant effects on gene expression and metabolism through a ceRNA effect, based on stoichiometric analysis of miR-122 and its well-known targets (44).…”
Section: Discussionmentioning
confidence: 99%